Ibogaine-Mediated ROS/Antioxidant Elevation in Isolated Rat Uterus Is β-Adrenergic Receptors and KATP Channels Mediated - Nikola Tatalović; Teodora Vidonja Uzelac; Zorana Oreščanin Dušić; Aleksandra Nikolić-Kokić; Mara Bresjanac; Duško Blagojević (MDPI AG, 2021)
Ibogaine effects are mediated by cellular receptors, ATP depletion followed by ROS production and antioxidant enzyme activity elevation in a dose and time dependent manner. Since the role of KATP channels and β-adrenoceptors in ROS cellular circuit was established here we explored their role in ibogaine pro-antioxidant effectiveness. Single dose of ibogaine (10 mg/L i.e., 28.8 μmol/L) was applied to isolated rat uterus (spontaneous and Ca2+-stimulated) and contractility and antioxidant enzymes activity were monitored during 4 h. Ibogaine increased amplitude and frequency of spontaneous active uteri immediately after addition that was prevented by propranolol (β1 and β2 adrenoceptors selective antagonists) and glibenclamide (KATP sensitive channels inhibitor; only frequency) pre-treatment. In Ca2+-stimulated uteri, ibogaine decreased both amplitude and frequency after 4 h. Pre-treatment with propranolol abolished ibogaine induced amplitude lowering, while glibenclamide had no effect. In both types of active uterus, ibogaine induced a decrease in SOD1 and an increase in CAT activity after 2 h. In Ca2+-stimulated uterus, there was also a decrease of SOD2 activity after 2 h. After 4 h, SOD1 activity returned to the baseline level, but GSH-Px activity increased. Pre-treatment with both propranolol and glibenclamide abolished observed changes of antioxidant enzymes activity suggesting that ibogaine pro-antioxidative effectiveness is β-adrenergic receptors and KATP channels mediated.